The sociology of families : key debates and contending perspectives / edited by Marina A. Adler, Karl Lenz. - Adler, Marina A.; Lenz, Karl, 1955- (Key debates and contending perspectives series., 2025)
This volume examines current research on key issues widely debated in contemporary family sociology. Contributors present emerging perspectives on the dynamics and challenges related to changing family forms and increasing family diversity in various countries or regions. The analyses reveal the multidimensional nature of living arrangements, parenting, and policies in a context of long-term social changes.